Impact of porcelain aorta on outcomes in transfemoral aortic valve implantation (TAVI) with balloon-expandable valves - Bernhard Schieffer; Thomas Kuntze; Tamer Owais; Philipp Lauten; Julian Kreutz; Lisa C Costello-Boerrigter; Mathias Schreiber; Guido Boerrigter; Christian Albert; Mohammad El Garhy; Björn Göbel; Harald Lapp; et al. (Open Heart)
Background Current guidelines recommend transcatheter aortic valve implantation (TAVI) for patients with aortic stenosis and porcelain aorta (PA). Neurological outcomes of patients with PA undergoing TAVI with modern valves require clarification as most trials examined balloon-expandable valves (BEV) and self-expandable valves in intermediate or high-risk patients, but not specifically in patients with PA. Our aim was to compare outcomes, including stroke and mortality, in well-matched patients with and without PA who received BEV during transfemoral TAVI procedures.Methods Consecutive patients undergoing TAVI were entered into a registry. For this single-centre (Zentralklinik Bad Berka, Germany), retrospective analysis, we only selected patients who received BEV. PA diagnosis was made when non-contrast axial CT images fulfilled Valve Academic Research Consortium-2 criteria for PA. There was 2:1 nearest neighbour matching of patients without and with PA. The primary outcome measure was 30-day mortality or stroke within 72 hours. Secondary outcome measures were 30-day mortality, stroke within 72 hours, technical success and 30-day device success.Results After matching patients with (n=141) and without PA (n=282), the primary outcome of mortality at <30 days or stroke within 72 hours was higher in PA versus non-PA (7.8% vs 2.5%; OR 3.32 (95% CI 1.25 to 8.85); p=0.019). With regard to secondary outcomes, PA was not associated with mortality at 30 days (4.3% vs 2.1%; OR 2.04 (95% CI 0.65 to 6.48); p=0.23); however, stroke within 72 hours was significantly higher in PA versus non-PA (3.5% vs 0.4%; OR 10.33 (95% CI 1.17 to 91.12); p=0.017). Technical and device success were uninfluenced by PA.Conclusions Transfemoral TAVI with BEV in patients with PA was associated with a higher risk of the primary combined endpoint of mortality at 30 days or stroke within 72 hours, which was primarily driven by stroke within 72 hours. These findings might influence cerebral embolic protection device use in patients with PA.